2016
DOI: 10.1111/jsr.12477
|View full text |Cite
|
Sign up to set email alerts
|

Impact of inflammation and oxidative stress on carotid intima‐media thickness in obstructive sleep apnea patients without metabolic syndrome

Abstract: Obstructive sleep apnea (OSA) increases the risk of cardiovascular diseases, and carotid intima-media thickness (IMT) is a good indicator of the severity of atherosclerotic disease. This study tested the hypothesis that inflammation and oxidative stress determined carotid IMT in patients with OSA. The carotid IMT, mean systolic and diastolic pressure (night and morning) were significantly higher and the level of thiols and high-density lipoprotein were significantly lower in our 121 OSA patients than in 27 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…These two mechanisms not only lead to the onset of systemic inflammation but also result in oxidative stress. Chang et al reported that inflammation and oxidative stress play an important role in the increasing carotid IMT in OSA patients (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These two mechanisms not only lead to the onset of systemic inflammation but also result in oxidative stress. Chang et al reported that inflammation and oxidative stress play an important role in the increasing carotid IMT in OSA patients (11).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been suggested that the values of arterial stiffness and compliance [pulse wave velocity (PWV) and carotid distensibility coefficient (DC)] are useful indices for predicting the future risk of cardiovascular events such as stroke and coronary heart disease (9,10). Increased IMT in OSA patients has been widely demonstrated (11)(12)(13)(14). Innovations in ultrasound technology, such as the US radiofrequency (RF)-data technology, allow for an automatic and accurate measurement of carotid IMT and arterial elasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, some evidence demonstrated that circulating L-selectin levels were significant and independent indicators of accentuated atherogenesis in patients with OSA [24,45]. However, some studies showing the correlation between circulating L-selectin and OSA were not detected, probably due to the defining criteria of the OSA were inconsistent [46,47]. In the present study, we found that the circulating L-selectin levels were significantly increased in the OSA group, and it was independently associated with the occurrence of the OSA and its severity.…”
Section: Discussionmentioning
confidence: 99%
“…Two papers in this issue (Chang et al, 2017;Kim et al, 2017) look at the relationship between snoring, sleep apnea and atherosclerosis. Kim et al measured carotid intimamedia thickness (IMT) in a sample of 180 non-apneic and non-snorers (snoring was recorded objectively by a microphone).…”
Section: Sleep and Breathing Disordersmentioning
confidence: 99%
“…Two papers in this issue (Chang et al ., ; Kim et al ., ) look at the relationship between snoring, sleep apnea and atherosclerosis. Kim et al .…”
mentioning
confidence: 99%